Putusan Bebas Pengadilan Negeri Gunung Sitoli Nomor: 119/PID.B/2019/PN.GST Tanggal 11 Mei 2022 terhadap Terdakwa Yang Melanggar Pasal 374 KUHP - Sebayang, Dona Martinus; Mulyadi, Mahmud; Andriati, Syarifah Lisa (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The problem in this study is how criminal responsibility and proof for embezzlement in employment relations in Decision Number 119 / Pid.B / 2019 / PN Gst, what is the role and function of Judges in the law. The results showed: The criminal liability of perpetrators of embezzlement in employment relations in Decision Number 119/Pid.B/2019/PN Gst, if you look at Article 374 of the Criminal Code as demanded by the Public Prosecutor is a threat through a maximum sentence of 5 years. The role of the Judge in law through his decision is based on Article 1 paragraph (8) of the Code of Criminal Procedure which states that the Judge is a state judicial official authorized by law to prosecute. The legal analysis of the decision of the Gunung Sitoli District Court Judge who decided to acquit the defendant Agustina Ndraha in Decision Number 119/Pid.B/2019/PN Gst was considered inappropriate, because the free verdict decided by the Panel of Judges regarding the embezzlement case in employment relations submitted by the Public Prosecutor on the basis that the Judge did not apply the law properly, namely in legal considerations on incriminating matters and mitigating the Defendant regarding the conviction of the Defendant.